The Autonomic Repercussions of Fetal and Maternal Interaction in Pre-eclampsia - Lakhno, Igor (De Gruyter, 2017)
Pre-eclampsia (PE) is one of the severe complications of pregnancy that leads to fetal deterioration. Th e aim of the investigation was to determine the role of maternal respiratory sinus arrhythmia (RSA) in regulation of fetal circulatory system in case of healthy pregnancy and in PE. Th e investigation of maternal and fetal HRV and umbilical venous blood fl ow velocity spectral analysis in 106 patients at 34-40 weeks of gestation was performed. 30 of them had healthy pregnancy and were involved in the Group I. In Group II 44 pregnant women with mild-moderate PE were observed. 32 patients with severe PE were monitored in Group III. Th e maternal sympathetic overactivity modulated HRV in PE. Th e suppression of RSA was explored in preeclamptic patients. Th e Doppler spectrograms of the umbilical veinous blod fl ow had the oscillatory peak with a frequency about 0.5 Hz. Th e above peak characterized the participation of the maternal RSA in fetal hemodynamics. Strong relationship between maternal RMSSD and amplitude of RSA associated peak, maternal and fetal RMSSDs was found in healthy pregnancy. No considerable relationship was revealed between the maternal RMSSD and the amplitude of 0.5 Hz frequency peak, the maternal and fetal RMSSDs in the patients with severe PE. Th e maternal RSA propagated its infl uence on the fetal umbilical venous blood fl ow and the fetal autonomic nervous regulation in normal gestation. Th e control of fetal hemodynamics diminished in the mild-moderate PE and even disappeared in severe PE.
Keywords: autonomic nervous regulation; maternal respiratory sinus arrhythmia; fetal umbilical venous hemodynamics; pre-eclampsia